Analisis Pembelajaran Mufradat Anak Usia Dini Menggunakan Youtube Berdasarkan Teori Behaviorisme Thorndike - Inas Dhia Fauziah; Maman Abdurrahman; Shofa Musthofa Khalid (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Learning Arabic vocabulary in early childhood is essential for developing basic language skills. However, more attention must be paid to applying digital media, such as YouTube, to language learning with a behaviorist approach, specifically Thorndike's theory. This study aims to analyze Arabic vocabulary teaching in early childhood using YouTube based on Thorndike's behaviorism theory at Asy-Syukuriyah TPA. The research method is descriptive qualitative, with a purposive sampling technique involving teachers as informants. Data were collected through observation, in-depth interviews, and documentation. The results showed that using YouTube as a medium for learning Arabic vocabulary is to the principles of the law of readiness, practice, and consequences in Thorndike's behaviorism theory. The law of readiness can be seen from the teacher ensuring the children's readiness before starting learning. Furthermore, the law of practice is seen by repeating material through videos to strengthen memory and questions about the material provided. Finally, the law of consequences is seen in the praise given by the teacher when children successfully answer the questions presented. In conclusion, if used strategically and systematically, YouTube as a learning media can be an effective tool in teaching Arabic in early childhood and can strengthen the association between stimulus and response through repetition. The findings have implications that YouTube-based learning based on Thorndike's theory of behaviorism has the potential to be applied more widely, with further research on different age groups and subjects as well as in-depth analysis of student characteristics.